PERANAN SISTEM INFORMASI MANAJEMEN PAI UNTUK MENINGKATKAN KUALITAS GURU DI SMP PLUS AL MUNAWAR - Andrias, Andrias Nurkamil Albusthomi (TEXTURA, 2021)
This study aims to determine the efforts of the PAI management system in improving teacher quality and to determine the implementation of the PAI management system in improving teacher quality at SMP Plus Al Munawar.Kec. Soreang Kab Bandung. The method in this research uses a qualitative approach. This qualitative research explains by compiling a design that is continuously adjusted to the conditions in the field and by data collection techniques, namely by observation, interviews and documentation study. The results of this study indicate that the efforts to improve SIM PAI at SMP Plus Al Munawar aim to build data and information flows so that they are able to integrate data and distribute information to and from various terminals quickly, accurately and safely. The implementation of the PAI management system at SMP Plus Al Munawar is as follows: a) determination of objectives and suggestions, b) formulation of strategies, c) planning, d) preparation of work programs, e) organizing, f) mobilizing human resources, g) organizing operational activities , h) supervision, and i) assessment.